Comparison of First Trimester Cervical Consistency Index and Cervical Length as a Predictor for Preterm Birth - Elhabashy, Ahmed; Elhabashy, Moustafa; Mansy, Amr; Elgazayerli, Wael; Swelem, Manal (Journal of Fetal Medicine, 2025)
Spontaneous preterm birth (sPTB) is a leading cause of neonatal morbidity and mortality. The low sensitivity of short cervical length (CL) for sPTB in low-risk populations highlights the need to explore other predictors. Since cervical softening occurs before its shortening, a marker for cervical compressibility, such as the cervical consistency index (CCI), could improve sPTB prediction.The aim of our study was to evaluate the role of CCI measurement in predicting sPTB in low-risk pregnant women during their first trimester scan. Additionally, CCI's effectiveness was compared with that of CL measured during the same visit. To our knowledge, this is the first study to prospectively assess the ability of the first-trimester (T1) CCI to predict sPTB in a low-risk population.Our study was a prospective cohort study that included 518 low-risk singleton pregnancies referred to a single tertiary center (Habashy 4D scan; Alexandria, Egypt) between September 2022 and September 2024. The low-risk population includes individuals without maternal medical disorders, maternal Mullerian anomalies, or a history of sPTB. CL and CCI were measured using transvaginal ultrasound during the T1 scan (11–14 weeks of gestation) from the internal to external os. CL was measured in the sagittal plane without applying probe pressure or fundal pressure. The CCI was calculated as the ratio of the anteroposterior diameter of the cervix at its midpoint under maximal probe pressure (maintained for 10 seconds) to the same diameter without pressure. Cases were then followed by phone calls every 2 weeks until delivery.A total of 450 cases (87%) delivered full term (≥ 37 weeks). Fifty-seven cases (11%) delivered late preterm (≥ 34 weeks–< 37 weeks). Eleven cases (2%) delivered early preterm (< 34 weeks). The diagnostic performance of T1-CCI surpasses that of T1-CL for predicting sPTB, as the area under the curve for full term versus sPTB and early versus late preterm were 0.858 and 0.738 versus 0.659 and 0.554. The optimal cutoffs for T1-CCI are 75% (for full term vs. preterm) and 67% (for early vs. late preterm). At these cutoffs, T1-CCI shows much higher sensitivity for predicting preterm birth than T1-CL (73.53% vs. 47.06%), with nearly similar specificities (76.89% vs. 83.78%). The specificity of combined T1-CL and T1-CCI is 100%.The T1-CCI is a better predictor of sPTB before 37 weeks and before 34 weeks than T1-CL in a low-risk population. The optimal cutoffs for T1-CCI are 75% (for full term vs. preterm) and 67% (for early vs. late preterm). The high sensitivity of T1-CCI reduces the false positive rate, thus avoiding unnecessary interventions. Further studies are needed before it can be implemented in routine obstetric practice.
Keywords: cervical consistency index; cervical length; spontaneous preterm birth; first trimester ultrasound